Inpatient versus outpatient induction of labour: a systematic review and meta-analysis - Susan Dong; Maria Khan; Farahnosh Hashimi; Caroline Chamy; Rohan D'Souza (BMC, 2020)
Abstract Background As the number of indications for labour induction continue to increase, the focus has shifted to performing these procedures in an outpatient setting. This study aims to systematically review published data from randomized controlled trials that compare outpatient with inpatient labour induction, to ascertain the role of outpatient labour induction for low-risk pregnancies. Methods We conducted a systematic review wherein we searched MEDLINE, EMBASE, Biosis Previews®, and International Pharmaceutical Abstracts from inception to January 2020 to identify randomized controlled trials that reported on maternal, fetal and resource-related outcomes following outpatient versus inpatient labour induction. Pooled incidences and mean differences were calculated using random-effects meta-analysis. Risk-of-bias was assessed using the Cochrane Risk of Bias tool. Subgroup analysis was conducted based on the method of induction. Results Of the 588 records identified, 12 publications, representing nine independent randomized controlled trials conducted in Australia, Europe and North America, were included. These reported on 2615 cases of labour induction (1320 outpatients versus 1295 inpatients). Overall, apart from a higher number of suspicious fetal heart rate tracings [RR = 1.43 (1.10, 1.86)] and a shorter mean length of hospital stay [MD = 282.48 min (160.23, 404.73) shorter] in the outpatient group, there were no differences in delivery method, adverse outcomes or resource-use between the two arms. On subgroup analysis, when comparing the use of balloon catheters in both arms, those induced as outpatients had fewer caesarean deliveries [RR = 0.52 (0.30, 0.90)], a shorter admission-to-delivery interval [MD = 370.86 min (19.19, 722.54) shorter], and a shorter induction to delivery interval [MD = 330.42 min (120.13, 540.71) shorter]. Conclusion Outpatient labour induction in resource-rich settings is at least as effective and safe, in carefully selected patient populations, when compared with inpatient labour induction. Whether outpatient labour induction results in lower rates of caesarean deliveries needs to be explored further. Trial registration This systematic review was prospectively registered in Prospero ( CRD42019118049 ).